Produksi Ikan Nila Dengan Kolam Terpal di Desa Kramajaya, Lombok Barat Untuk Mencegah Stunting - Fariq Azhar; Muhammad Marzuki; Andre Rachmat Scabra; Nuri Muahiddah; Rangga Idris Affandi; Muhammad Sumsanto (Jurnal Gema Ngabdi, 2023)
Kramajaya Village is one of the stunting loci in Narmada District, West Lombok Regency. Stunting is a problem of chronic malnutrition caused by inadequate nutritional intake over a long period of time due to providing food that is not in accordance with nutritional needs. The way to overcome and prevent stunting from a food perspective is to provide nutritious food to pregnant women, breastfeeding mothers and toddlers. These nutritious foods can include eggs, beef, chicken, seawater fish or freshwater fish. Tilapia is a fish that has high nutritional value and is classified as a fish that is low in cholesterol so it is healthy to consume. The results of discussions with the Mandiri Jaya Youth Organization, Kramajaya Village, Narmada District, West Lombok Regency, has abundant water sources. Apart from that, in Kramajaya hamlet there are many yards of residents' houses that have not been utilized optimally. There are no residents who know that the yard can be used to produce tilapia due to lack of knowledge about the technology of cultivating tilapia using tarpaulin ponds. Therefore, there is a need for knowledge transfer and assistance so that village residents, especially the Mandiri Jaya Youth Organization, Kramajaya Village, can produce tilapia fish in tarpaulin ponds to fulfill community nutrition, especially to prevent stunting and help improve the family economy. This counseling will be carried out using the Focus Group Discussion (FGD) method. Tilapia fish production using tarpaulin ponds in Kramajaya Village, West Lombok, is an effective solution in preventing stunting and improving community nutrition